Pengembangan Video Animasi “Vivi dan Jeje” untuk Pembelajaran Menulis Teks Petunjuk bagi Siswa Kelas IV SDN Bunulrejo 3 Malang - Mohamad Vijay; Titis Angga Rini; Puri Selfi Cholifah; Mohamad Vijay; Titis Angga Rini (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2023)
Abstract: This research is based on a preliminary study during KPL (Field Practice Study), interviews with fourth grade teachers, and analysis of the needs of fourth grade students at SDN Bunulrejo 3 Malang, which shows that the use of media is still limited to learning to write instructional texts, so students feel bored. in learning. Based on these problems, an animated video "Vivi and Jeje" was developed for learning to write instructional texts for fourth grade students at SDN Bunulrejo 3 Malang. This study aims to produce and test animated video products for learning to write instructional texts for fourth grade elementary school students that are valid based on the validation of material experts and media experts, interesting and practical based on teacher and student responses. This research uses the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). Data collection techniques used in this study were interviews, questionnaires, observations, tests and documentation. The results showed that the product validity from the results of the material expert validation was 91.66 percent and the media expert validation results were 100 percent. The attractiveness and practicality of the results of the teacher's response questionnaire are 96.36 percent, the results of the small group student response questionnaire are 96.36 percent, and the results of the large group student questionnaire response are 96.83 percent. Based on the results of the research, it can be concluded that the product validity is categorized as valid without revision, the attractiveness and practicality of the product are categorized as very attractive and practical. Abstrak: Penelitian ini dilatarbelakangi berdasarkan studi pendahuluan selama KPL (Kajian Praktik Lapangan), wawancara dengan guru kelas IV, dan analisis kebutuhan siswa kelas IV SDN Bunulrejo 3 Malang, yang menunjukkan bahwa penggunaan media masih terbatas pada pembelajaran menulis teks petunjuk, sehingga siswa merasa bosan dalam pembelajaran. Berdasarkan permasalahan tersebut, dilakukan pengembangan video animasi “Vivi dan Jeje” untuk pembelajaran menulis teks petunjuk bagi siswa kelas IV SDN Bunulrejo 3 Malang. Penelitian ini bertujuan untuk menghasilkan dan mengujicobakan produk video animasi untuk pembelajaran menulis teks petunjuk bagi siswa kelas IV SD yang valid berdasarkan validasi ahli materi dan ahli media, menarik dan praktis berdasarkan respon guru dan siswa. Penelitian ini menggunakan model pengembangan ADDIE (Analyze, Design, Development, Implementation, and Evaluation). Teknik pengumpulan data yang dilakukan dalam penelitian ini berupa wawancara, angket, observasi, tes dan dokumentasi. Hasil penelitian menunjukkan bahwa kevalidan produk dari hasil validasi ahli materi sebesar 91,66 persen dan hasil validasi ahli media sebesar 100 persen. Kemenarikan dan kepraktisan dari hasil angket respon guru sebesar 96,36 persen, hasil angket respon siswa kelompok kecil sebesar 96,36 persen, dan hasil angket respon siswa kelompok besar sebesar 96,83 persen. Berdasarkan hasil penelitian tersebut, dapat disimpulkan bahwa kevalidan produk dikategorisasikan valid tanpa revisi, kemenarikan dan kepraktisan produk dikategorisasikan sangat menarik dan praktis.